„Echte Thymushyperplasie“: Differenzialdiagnose der Thymusvergrößerung bei Säuglingen und Kindern = True thymic hyperplasia - differential diagnosis of thymic mass lesions in neonates and children - Weis, Cleo-Aron Thias; Marx, Alexander (Der Pathologe, 2017)
Reactive and neoplastic thymic pathologies are the main considerations in the case of masses in the anterior and middle part of the mediastinum, while neurogenic tumors are predominant in the posterior mediastinum (which are not dealt with here). In neonates and infants, the commonest pathologies in the anterior mediastinum comprise germ cell tumors (mainly teratomas), congenital thymic cysts and true thymic hyperplasia (TTH). In toddlers, teratomas, yolk sac tumors and cysts predominate. In children over 5 years of age, lymphomas are the commonest mass lesions whereas thymomas and thymic carcinomas are rare. In addition, inflammation-linked hyperplasia in myasthenia gravis and rebound thymic hyperplasia after chemotherapy must be considered. Although rare at all ages, sarcomas must be considered in the differential diagnosis from birth onwards and throughout adolescence. Based on the report of a rare case of recurrent TTH, the differential diagnosis of this benign but potentially life-threatening condition is discussed.